Intramuscular hemangioma mimicking synovial sarcoma on fine-needle aspiration cytology - Monika Rathi; Ankita Mittal; Satish Kumar Budania; Niyati Sakarwal; Jaskirat Singh; Jyotsana Khattri (Wolters Kluwer Medknow Publications, 2015)
A 13-year-old boy presented to our hospital with clinical complaint of lump in knee joint and associated pain for 6 years. Fine-needle aspiration cytology was done and cytology smears showed biphasic pattern composed of spindle cells, epithelial elements, and numerous mast cells. Hence, it was reported as synovial sarcoma and histopathology was advised. Lump was excised successfully. Histopathological sections showed numerous capillary sized blood vessels, cavernous blood vessels, thick walled blood vessels present between skeletal muscle, and adipose tissue. Hence, the diagnosis of intramuscular haemangioma was made. Follow-up was done for 1 year. No recurrence or complications were seen.